Land-use change impacts from sustainable hydropower production in EU28 region: an empirical analysis - Mohd Alsaleh; Abdulwakil, Muhammad Mansur; Abdul-Rahim, Abdul Samad (MDPI AG, 2021)
Under the current European Union (EU) constitution approved in May 2018, EU countries ought to guarantee that estimated greenhouse-gas releases from land use, land-use change, or forestry are entirely compensated by an equivalent accounted removal of carbon dioxide (CO2) from the air during the period between 2021 and 2030. This study investigates the effect of sustainable hydropower production on land-use change in the European Union (EU28) region countries during 1990–2018, using the fully modified ordinary least squares (FMOLS). The results revealed that land-use change incline with an increase in hydropower energy production. In addition, economic growth, carbon dioxide emissions, and population density are found to be increasing land-use changes, while institutional quality is found to be decreasing land-use change significantly. The finding implies that land-use change in EU28 region countries can be significantly increased by mounting the amount of hydropower energy production to achieve Energy Union aims by 2030. This will finally be spread to combat climate change and environmental pollution. The findings are considered robust as they were checked with DOLS and pooled OLS. The research suggests that the EU28 countries pay attention to the share of hydropower in their renewable energy combination to minimize carbon releases. Politicians and investors in the EU28 region ought to invest further in the efficiency and sustainability of hydropower generation to increase its production and accessibility without further degradation of forest and agricultural conditions. The authorities of the EU28 region should emphasize on efficiency and sustainability of hydropower energy with land-use management to achieve the international commitments for climate, biodiversity, and sustainable development, reduce dependence on fossil fuel, and energy insecurity.